Identity-Based Brand Management : Fundamentals-Strategy-Implementation-Controlling - Burmann, Christoph; Riley, Nicola-Maria; Halaszovich, Tilo; Schade, Michael (Springer Fachmedien Wiesbaden, 2017)
This textbook provides a theoretically based and comprehensive overview of the identity-based brand management. The focus is on the design of brand identity as the internal side of a brand and the resulting external brand image amongst buyers and other external audiences. The authors show that the concept of identity-based brand management has proven to be the most efficient management model to make brands a success. Numerous illustrative practicable examples demonstrate its applicability. The content - Foundation of identity-based brand management - The concept of identity-based brand management - Strategic brand management - Operational brand management - Identity-based brand controlling - Identity-based trademark protection - International identity-based brand management The authors Prof. Dr. Christoph Burmann is the holder of the Chair of Innovative Brand Management (LiM) at the University of Bremen/Germany. Dr. Nicola Riley is post-doc at the Chair of Innovative Brand Management (LiM) at the University of Bremen/Germany. Dr. Tilo Halaszovich is post-doc at the Chair of International Management and Governance (IMG) at the University of Bremen/Germany. Dr. Michael Schade is post-doc at the Chair of Innovative Brand Management (LiM) at the University of Bremen/Germany.
Keywords: Brand name products -- Management.; Branding (Marketing); Business.; Marketing.; elektronické knihy; electronic books